State-of-Art Bio-Assay Systems and Electrochemical Approaches for Nanotoxicity Assessment - Shinde, Ravikumar B.; Veerapandian, Murugan; Kaushik, Ajeet; Manickam, Pandiaraj (Frontiers in Bioengineering and Biotechnology, 2020)
Innovations in the field of nanotechnology, material science and engineering has rendered fruitful utilities in energy, environment and healthcare. Particularly, emergence of surface engineered nanomaterials offered novel varieties in the daily consumables and healthcare products including therapeutics and diagnostics. However, the nanotoxicity and bioactivity of the nanomaterials upon interaction with biological system has raised critical concerns to individual as well as to the environment. Several biological models including plant and animal sources have been identified to study the toxicity of novel nanomaterials, correlating the physio-chemical properties. Biological interaction of nanomaterials and its mediated physiological functions are studied using conventional cell/molecular biological assays to understand the expression levels of genetic information specific to intra/extra cellular enzymes, cell viability, proliferation and function. However, modern research still demands advanced bioassay methods to screen the acute and chronic effects of nanomaterials at the real-time. In this regard, bioelectrochemical techniques, with the recent advancements in the microelectronics, proved to be capable of providing non-invasive measurement of the nanotoxicity effects (in vivo and in vitro) both at single cellular and multicellular levels. This review attempted to provide a detailed information on the recent advancements made in development of bioassay models and systems for assessing the nanotoxicology. With a short background information on engineered nanomaterials and physiochemical properties specific to consumer application, present review highlights the multiple bioassay models evolved for toxicological studies. Emphasize on multiple mechanisms involved in the cell toxicity and electrochemical probing of the biological interactions, revealing the cytotoxicity were also provided. Limitations in the existing electrochemical techniques and opportunities for the future research focusing the advancement in single molecular and whole cell bioassay has been discussed.